MooTools Essentials - Newton, Aaron (Springer, 2017)
Mootools is a light, modular JavaScript framework that makes adding Ajax, animations, and interactive elements to your site a breeze. But it's more than fancy effects and shortcuts; Mootools enhances the JavaScript language and makes writing clean, object–oriented code almost pleasant. Unlocking the power of Mootools, and therefore JavaScript, isn't that hard, but knowing where to start can be. Mootools Essentials aims to help you accomplish that task with the following: